2021
DOI: 10.3389/fcvm.2021.705666
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic, Biochemical, and Electrocardiographic Correlates Associated With Progressive Pulmonary Arterial Hypertension

Abstract: Background: Pulmonary arterial hypertension (PAH) is a progressive proliferative vasculopathy associated with mechanical and electrical changes, culminating in increased vascular resistance, right ventricular (RV) failure, and death. With a main focus on invasive tools, there has been an underutilization of echocardiography, electrocardiography, and biomarkers to non-invasively assess the changes in myocardial and pulmonary vascular structure and function during the course of PAH.Methods: A SU5416-hypoxia rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The ethanol-induced RV hypertrophy, which is expressed as a higher RV/body weight ratio and Fulton index (RV/LV+ Septum) (Figure 1B,C), likely resulted from increased RV afterload, a hallmark cardiac phenotype of PAH (Ryan & Archer, 2014). As discussed earlier, elevated RV afterload is supported by ethanol-induced: (1) progressive reductions in both PAAT and PAAT/PET (Figure 2A,B), which are inversely related to RVSP derived from right ventricle catheterization (Spyropoulos et al, 2020;Zaky et al, 2021), and (2) elevation in mPAP (Figure 2D). Our echocardiographic findings of ethanolinduced progressive increases in RV chamber size (Figure 2C) likely F I G U R E 3 Ethanol causes pulmonary arteriole thickening and RV cardiomyocyte hypertrophy.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The ethanol-induced RV hypertrophy, which is expressed as a higher RV/body weight ratio and Fulton index (RV/LV+ Septum) (Figure 1B,C), likely resulted from increased RV afterload, a hallmark cardiac phenotype of PAH (Ryan & Archer, 2014). As discussed earlier, elevated RV afterload is supported by ethanol-induced: (1) progressive reductions in both PAAT and PAAT/PET (Figure 2A,B), which are inversely related to RVSP derived from right ventricle catheterization (Spyropoulos et al, 2020;Zaky et al, 2021), and (2) elevation in mPAP (Figure 2D). Our echocardiographic findings of ethanolinduced progressive increases in RV chamber size (Figure 2C) likely F I G U R E 3 Ethanol causes pulmonary arteriole thickening and RV cardiomyocyte hypertrophy.…”
Section: Discussionmentioning
confidence: 64%
“…Rat chest hair was removed using Veet® hair removal cream. Echocardiography data analysis was conducted using VivoLab Software (Zaky et al., 2021).…”
Section: Methodsmentioning
confidence: 99%
“…PAAT is the time interval between the onset of systolic pulmonary arterial flow and peak flow velocity. Previous studies have demonstrated that PAAT is inversely proportional to pulmonary vascular resistance (28)(29)(30). If the pulmonary vascular resistance increases, the pulmonary artery pressure also increases.…”
Section: Animal Model and Treatment Strategy A Total Of 12mentioning
confidence: 97%
“…PAAT was measured near the pulmonary valve on the left chest. According to the current guidelines of the American Society of Echocardiography, mPAP can be calculated according to the following formula: mPAP = 72-(0.42×PAAT, PAAT < 120 ms) [23,25]. After the detection, the rats were sacri ced under deep anesthesia (I.P.…”
Section: Doppler Echocardiography Measurementmentioning
confidence: 99%